Collective strong coupling of cold potassium atoms in a ring cavity - R Culver; A Lampis; B Megyeri; K Pahwa; L Mudarikwa; M Holynski; Ph W Courteille; J Goldwin (New Journal of Physics, 2016)
We present experiments on ensemble cavity quantum electrodynamics with cold potassium atoms in a high-finesse ring cavity. Potassium-39 atoms are cooled in a two-dimensional magneto-optical trap and transferred to a three-dimensional trap which intersects the cavity mode. The apparatus is described in detail and the first observations of strong coupling with potassium atoms are presented. Collective strong coupling of atoms and light is demonstrated via the splitting of the cavity transmission spectrum and the avoided crossing of the normal modes.